New Year's Countdown Day 11: Undecagon

Geometry Level 4

A regular 11-sided polygon A B C D E F G H I J K ABCDEFGHIJK is inscribed in a unit circle, as shown below.

If A B × A C × A D × A E × A F = k AB \times AC \times AD \times AE \times AF = \sqrt{k}

for some positive integer k , k, find the sum of digits of k . k.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

8 solutions

Steven Yuan
Dec 13, 2017

Relevant wiki: Roots of Unity

We can use complex numbers to model this problem. First, let ω = e 2 π i / 11 . \omega = e^{2\pi i/11}. Place the circle on the complex grid with its center at 0, and let A A be located at the complex number 1. Then, the points on the undecagon are the 11th roots of unity, so they are of the form ω n , \omega^n, where 1 n 11. 1 \leq n \leq 11. We can calculate the distance between A A and each of the other points by finding the difference between the points and taking the absolute value:

A B = 1 ω A C = 1 ω 2 A D = 1 ω 3 , \begin{aligned} AB &= |1 - \omega| \\ AC &= |1 - \omega^2| \\ AD &= |1 - \omega^3|, \end{aligned}

and so on. To calculate the desired product, we first note that

A B × A C × A D × × A K = ( A B × A C × A D × A E × A F ) 2 AB \times AC \times AD \times \cdots \times AK = (AB \times AC \times AD \times AE \times AF)^2

by symmetry i.e. A B = A K , AB = AK, etc. To calculate the left hand side product, we use the fact that the polynomial with roots that are the 11th roots of unity excluding 1 is

f ( x ) = x 11 1 x 1 = x 10 + x 9 + x 8 + + x + 1 , f(x) = \dfrac{x^{11} - 1}{x - 1} = x^{10} + x^9 + x^8 + \cdots + x + 1,

since x 11 1 x^{11} - 1 has all 11 11th roots of unity as roots, and we must exclude 1 as that represents point A . A. We can factor f f as

f ( x ) = ( x ω ) ( x ω 2 ) ( x ω 3 ) ( x ω 10 ) . f(x) = (x - \omega)(x - \omega^2)(x - \omega^3)\cdots(x-\omega^{10}).

Finally, since

A B × A C × A D × × A K = 1 ω 1 ω 2 1 ω 3 1 ω 10 = ( 1 ω ) ( 1 ω 2 ) ( 1 ω 3 ) ( 1 ω 10 ) = f ( 1 ) = 1 10 + 1 9 + 1 8 + + 1 + 1 = 11 , \begin{aligned} AB \times AC \times AD \times \cdots \times AK &= |1 - \omega||1 - \omega^2||1 - \omega^3|\cdots|1 - \omega^{10}| \\ &= |(1 - \omega)(1 - \omega^2)(1 - \omega^3)\cdots(1 - \omega^{10})| \\ &= |f(1)| \\ &= |1^{10} + 1^9 + 1^8 + \cdots + 1 + 1| \\ &= 11, \end{aligned}

we conclude A B × A C × A D × A E × A F = 11 , AB \times AC \times AD \times AE \times AF = \sqrt{11}, so k = 11 k = 11 and the sum of its digits is 1 + 1 = 2 . 1 + 1 = \boxed{2}.

Can you please explain in baby steps.

A Former Brilliant Member - 3 years, 5 months ago

Log in to reply

I'm assuming that you have some knowledge of the roots of unity ; if not, go read up on those. Otherwise, I have revised my solution a bit to give some justification of some of the steps. I hope this helps!

Steven Yuan - 3 years, 5 months ago

There is a typo: first line ω = e 2 π i 11 \omega = e^{\frac{2\pi i}{11}} .

Elegant solution!

I end up at 32 s i n ( π 11 ) s i n ( 2 π 11 ) s i n ( 3 π 11 ) s i n ( 4 π 11 ) s i n ( 5 π 11 ) 32sin(\frac{\pi}{11})sin(\frac{2\pi}{11})sin(\frac{3\pi}{11})sin(\frac{4\pi}{11})sin(\frac{5\pi}{11}) But you had used another way to solve it.

Kelvin Hong - 3 years, 5 months ago

Log in to reply

Thank you for the correction!

Steven Yuan - 3 years, 5 months ago

I reached to the same step and couldn't do more. Then I used a calculator and was surprised to see the answer as a whole number. So there must be an elegant way to solve this manually. Could you share it if you've found it?

Subin Manandhar - 3 years, 5 months ago

Log in to reply

Haha, I will give it a try, I also think this can achieve the answer :)

Kelvin Hong - 3 years, 5 months ago

Log in to reply

@Kelvin Hong I got it. You have to use the 2sinA.sinB = sin(A+B) + sin(A-B) and similar formulae for two factors at a time, then distribute them and continue this until you get every term in a sum form. Then square it (that expression gives sqrt k, we have to find k) and change into cosines and sines over and over again to get to the answer. I know it is a very long solution, but it is very satisfying when you finally complete it. The solution above seems elegant but I don't actually understand it completely. So.

Subin Manandhar - 3 years, 5 months ago

I just did it by computer calculation, I'm really in awe of your beautiful solution.

Sam Adriaensen - 3 years, 5 months ago

Log in to reply

Thanks! Usually when a problem involves regular polygons, we think to use roots of unity, because they form regular polygons when plotted on a complex plane.

Steven Yuan - 3 years, 5 months ago

Didn't think to factor the polynomial with the roots of unity like that. Elegant!

Will van Noordt - 3 years, 5 months ago

Simple, standard solution. Great!

Sharky Kesa - 3 years, 5 months ago
Tanuel Chi
Dec 26, 2017

A B × A C × A D × A E × A F = 32 r 5 sin ( π 11 ) sin ( 2 π 11 ) sin ( 3 π 11 ) sin ( 4 π 11 ) sin ( 5 π 11 ) AB\times AC\times AD\times AE\times AF=32r^5\sin(\frac{\pi}{11})\sin(\frac{2\pi}{11})\sin(\frac{3\pi}{11})\sin(\frac{4\pi}{11})\sin(\frac{5\pi}{11}) = 16 r 5 ( cos ( π 11 ) cos ( 3 π 11 ) ) sin ( 3 π 11 ) sin ( 4 π 11 ) sin ( 5 π 11 ) =16r^5(\cos(\frac{\pi}{11})-\cos(\frac{3\pi}{11}))\sin(\frac{3\pi}{11})\sin(\frac{4\pi}{11})\sin(\frac{5\pi}{11}) = 8 r 5 ( sin ( 4 π 11 ) + sin ( 2 π 11 ) sin ( 6 π 11 ) ) sin ( 4 π 11 ) sin ( 5 π 11 ) =8r^5(\sin(\frac{4\pi}{11})+\sin(\frac{2\pi}{11})-\sin(\frac{6\pi}{11}))\sin(\frac{4\pi}{11})\sin(\frac{5\pi}{11}) = 4 r 5 ( 1 cos ( 8 π 11 ) + cos ( 2 π 11 ) cos ( 6 π 11 ) cos ( 2 π 11 ) + cos ( 10 π 11 ) ) sin ( 5 π 11 ) =4r^5(1-\cos(\frac{8\pi}{11})+\cos(\frac{2\pi}{11})-\cos(\frac{6\pi}{11})-\cos(\frac{2\pi}{11})+\cos(\frac{10\pi}{11}))\sin(\frac{5\pi}{11}) = 2 r 5 ( 2 sin ( 5 π 11 ) sin ( 13 π 11 ) + sin ( 3 π 11 ) + sin ( π 11 ) + sin ( 15 π 11 ) sin ( 5 π 11 ) ) =2r^5(2\sin(\frac{5\pi}{11})-\sin(\frac{13\pi}{11})+\sin(\frac{3\pi}{11})+\sin(\frac{\pi}{11})+\sin(\frac{15\pi}{11})-\sin(\frac{5\pi}{11})) = 2 r 5 ( sin ( π 11 ) + sin ( 2 π 11 ) + sin ( 3 π 11 ) sin ( 4 π 11 ) + sin ( 5 π 11 ) ) =2r^5(\sin(\frac{\pi}{11})+\sin(\frac{2\pi}{11})+\sin(\frac{3\pi}{11})-\sin(\frac{4\pi}{11})+\sin(\frac{5\pi}{11})) So, k = 4 r 10 ( sin ( π 11 ) + sin ( 2 π 11 ) + sin ( 3 π 11 ) sin ( 4 π 11 ) + sin ( 5 π 11 ) ) 2 k=4r^{10}(\sin(\frac{\pi}{11})+\sin(\frac{2\pi}{11})+\sin(\frac{3\pi}{11})-\sin(\frac{4\pi}{11})+\sin(\frac{5\pi}{11}))^2 2 sin ( i π 11 ) sin ( j π 11 ) = cos ( ( i j ) π 11 ) cos ( ( i + j ) π 11 ) = c i j c i + j 2\sin(\frac{i\pi}{11})\sin(\frac{j\pi}{11})=\cos(\frac{(i-j)\pi}{11})-\cos(\frac{(i+j)\pi}{11})=c_{i-j}-c_{i+j} Therefore k = i = 1 5 j = 1 5 ( ) δ i 4 + δ j 4 ( c i j c i + j ) = i = 1 5 ( 1 c 2 i ) + i = 1 4 j = i + 1 5 ( ) δ i 4 + δ j 4 ( c i j c i + j ) k=\sum_{i=1}^5\sum_{j=1}^5(-)^{\delta_{i4}+\delta_{j4}}(c_{i-j}-c_{i+j})=\sum_{i=1}^5(1-c_{2i})+\sum_{i=1}^4\sum_{j=i+1}^5(-)^{\delta_{i4}+\delta_{j4}}(c_{i-j}-c_{i+j}) where δ x y \delta_{xy} stands for dirac delta function, which equals to 1 when x=y, and equals to 0 otherwise. = 2 r 10 ( 5 c 2 c 4 c 6 c 8 c 10 + 2 ( c 1 c 3 + c 2 c 4 c 3 + c 5 + c 4 c 6 + c 1 c 5 c 2 + c 6 + c 3 c 7 c 1 + c 7 + c 2 c 8 c 1 + c 9 ) ) =2r^{10}(5-c_2-c_4-c_6-c_8-c_{10}+2(c_1-c_3+c_2-c_4-c_3+c_5+c_4-c_6+c_1-c_5-c_2+c_6+c_3-c_7-c_1+c_7+c_2-c_8-c_1+c_9)) = 2 r 10 ( 5 + c 2 2 c 3 c 4 c 6 3 c 8 + 2 c 9 c 10 ) =2r^{10}(5+c_2-2c_3-c_4-c_6-3c_8+2c_9-c_{10}) Where c n = cos ( n π 11 ) c_n=\cos(\frac{n\pi}{11}) . So, k / r 10 = 12 + 2 ( 1 + cos ( π 11 ) cos ( 2 π 11 ) + cos ( 3 π 11 ) cos ( 4 π 11 ) + cos ( 5 π 11 ) ) k/r^{10}=12+2(-1+\cos(\frac{\pi}{11})-\cos(\frac{2\pi}{11})+\cos(\frac{3\pi}{11})-\cos(\frac{4\pi}{11})+\cos(\frac{5\pi}{11})) = 12 4 ( sin ( π 22 ) sin ( π 22 ) + sin ( π 22 ) sin ( 5 π 22 ) + sin ( π 22 ) sin ( 9 π 22 ) ) =12-4(\sin(\frac{\pi}{22})\sin(\frac{\pi}{22})+\sin(\frac{\pi}{22})\sin(\frac{5\pi}{22})+\sin(\frac{\pi}{22})\sin(\frac{9\pi}{22})) = 12 4 sin ( π 11 ) sin ( π 11 ) sin ( π 22 ) ( sin ( π 22 ) + sin ( 5 π 22 ) + sin ( 9 π 22 ) ) =12-4\frac{\sin(\frac{\pi}{11})}{\sin(\frac{\pi}{11})}\sin(\frac{\pi}{22})(\sin(\frac{\pi}{22})+\sin(\frac{5\pi}{22})+\sin(\frac{9\pi}{22})) = 12 2 sin ( π 22 ) sin ( π 11 ) ( cos ( π 22 ) cos ( 3 π 22 ) + cos ( 3 π 22 ) cos ( 7 π 22 ) + cos ( 7 π 22 ) cos ( 11 π 22 ) ) =12-2\frac{\sin(\frac{\pi}{22})}{\sin(\frac{\pi}{11})}(\cos(-\frac{\pi}{22})-\cos(\frac{3\pi}{22})+\cos(\frac{3\pi}{22})-\cos(\frac{7\pi}{22})+\cos(\frac{7\pi}{22})-\cos(\frac{11\pi}{22})) = 12 1 cos ( π 22 ) ( cos ( π 22 ) cos ( π 2 ) ) = 11 =12-\frac{1}{\cos(\frac{\pi}{22})}(\cos(\frac{\pi}{22})-\cos(\frac{\pi}{2}))=11 We got k=11, then the sum of its digits is 2.

Can you make your solution a bit mare clear

Abhinav Parri - 3 years, 5 months ago

I lost you when you suddenly changed to c's. Can you make that clear?

Subin Manandhar - 3 years, 5 months ago

Log in to reply

ok it seems clear now

Tanuel Chi - 3 years, 5 months ago

Mathematica:

s=CirclePoints@11; RootReduce[Times@@EuclideanDistance@@@Table[s[[{1,i}]],{i,2,6}]]

A good idea, but the command CirclePoints doesn't work!!!

A Former Brilliant Member - 3 years, 5 months ago

Log in to reply

It works on mathematica 10.4 or later version. You can also try it online on wolfram sandbox or run the code on wolfram cloud app

Χωρις Ονομας - 3 years, 5 months ago

Log in to reply

Εντάξει, ευχαριστώ!

A Former Brilliant Member - 3 years, 5 months ago
Rocco Dalto
Dec 29, 2017

In general, for any regular n n -gon inscribed in a circle with radius r r we can write a program using the algorithm below:

Let k n . k \leq n.

Let u 0 = 2 r sin ( π n ) u_{0} = 2r \sin(\dfrac{\pi}{n}) and for ( 1 j k 1 ) (1 \leq j \leq k - 1) u j = u 0 2 + u j 1 2 2 u 0 u j 1 cos ( ( n 2 ) π n ( j 1 ) π n ) u_{j} = \sqrt{u_{0}^2 + u_{j - 1}^2 - 2 u_{0} u_{j - 1}\cos(\dfrac{(n - 2)\pi}{n} - (j - 1)\dfrac{\pi}{n})}

and the product P = j = 0 k 1 u j P = \prod_{j = 0}^{k - 1} u_{j} and this problem wants P 2 = ( j = 0 k 1 u j ) 2 . P^2 = (\prod_{j = 0}^{k - 1} u_{j})^2.

Note: After doing the problem I wrote a program for the general case based on the algorithm above.

А good idea, however, the text will look much better if you use the LaTeX command \leq for \leq instead of < = <= . In parallel, \geq for \geq or if you prefer \leqslant for \leqslant , and in parallel \geqslant for \geqslant .

A Former Brilliant Member - 3 years, 5 months ago

Log in to reply

Thanks. I didn't know there was a LaTex command for \leq and \geq .

Rocco Dalto - 3 years, 5 months ago

Log in to reply

I suppose you edit a text by means of WinEdt?! Is so, then you can find there a lot of information about commands. If not, perhaps you can find some instructions on the web.

A Former Brilliant Member - 3 years, 5 months ago

We can apply the cosine theorem to find A B 2 , A C 2 , A D 2 , A E 2 , A F 2 AB^2,AC^2,AD^2,AE^2,AF^2 . So A B 2 = 2 ( 1 cos 2 π 11 ) , A C 2 = 2 ( 1 cos 4 π 11 ) , A D 2 = 2 ( 1 cos 6 π 11 ) , A E 2 = 2 ( 1 cos 8 π 11 ) , A F 2 = 2 ( 1 cos 10 π 11 ) AB^2=2(1-\cos\frac{2\pi}{11}),\,AC^2=2(1-\cos\frac{4\pi}{11}),\,AD^2=2(1-\cos\frac{6\pi}{11}),\,AE^2=2(1-\cos\frac{8\pi}{11}),\,AF^2=2(1-\cos\frac{10\pi}{11}) . Multiplication and application of theorems for the transformation a product of trigonometric functions into a sum, give rise to the equality A B 2 A C 2 A D 2 A E 2 A F 2 = 2 ( 5 + sin π 22 sin 3 π 22 + sin 5 π 22 sin 7 π 22 + sin 9 π 22 ) AB^2AC^2AD^2AE^2AF^2=2(5+\sin\frac{\pi}{22}-\sin\frac{3\pi}{22}+\sin\frac{5\pi}{22}-\sin\frac{7\pi}{22}+\sin\frac{9\pi}{22}) . To find the last trigonometric sum, we denote z = e i π 22 e i 3 π 22 + e i 5 π 22 e i 7 π 22 + e i 9 π 22 z=e^{i\frac{\pi}{22}}-e^{i\frac{3\pi}{22}}+e^{i\frac{5\pi}{22}}-e^{i\frac{7\pi}{22}}+e^{i\frac{9\pi}{22}} . So z = e i π 22 ( 1 + e i 5 π 11 ) 1 + e i π 11 z=\dfrac{e^{i\frac{\pi}{22}}(1+e^{i\frac{5\pi}{11}})}{1+e^{i\frac\pi{11}}} . The imaginary part of z z is the sum sin π 22 sin 3 π 22 + sin 5 π 22 sin 7 π 22 + sin 9 π 22 \sin\frac{\pi}{22}-\sin\frac{3\pi}{22}+\sin\frac{5\pi}{22}-\sin\frac{7\pi}{22}+\sin\frac{9\pi}{22} , and the imaginary part of the right-side expression is 1 2 \frac12 , so that A B 2 A C 2 A D 2 A E 2 A F 2 = 11 = k AB^2AC^2AD^2AE^2AF^2=11=k , meaning the sum of digits of k k is 2 2 .

Suby Chandy
Dec 26, 2017

Let the centre of the circle be O. Angle AOB = 360/11 = 32.73 deg. AB = 2 x Sin(AOB/2) AC = 2 x Sin(2 x AOB/2) . . AF = 2 x Sin(5 x AOB/2) Substituting the value of angle AOB, AB x AC x AD x AE x AF = 3.3166 Hence k = 3.3166^2 = 11

A good idea, what the value of sin ( A O B ) \sin(AOB) is?!

A Former Brilliant Member - 3 years, 5 months ago
Noro Slivka
Dec 30, 2017

Given A B × A C × A D × A E × A F = k AB \times AC \times AD \times AE \times AF = \sqrt{k} , A B 2 × A C 2 × A D 2 × A E 2 × A F 2 = k AB^2 \times AC^2 \times AD^2 \times AE^2 \times AF^2 = k .

To compute the length of A X AX for X { B , C , D , E , F } X \in \left\{B, C, D, E, F\right\} , we use the formula c 2 = a 2 + b 2 2 a b cos θ c^2 = a^2 + b^2 - 2ab \cos \theta where a a and b b are both the radius. Let P P be the centre of the circle. Then, the angle θ \theta is equal to the angle A P X APX , which is n 11 2 π r a d \frac{n}{11}2\pi rad , where n n is 1 for X = B X=B , 2 for X = C X=C and so on around the circle. This gives us the equation:

n = 1 5 2 ( 1 c o s ( n 11 2 π ) ) = 11 \prod_{n=1}^{5}{2\left(1-cos\left(\frac{n}{11}2\pi\right)\right)} = 11

The sum of the digits of 11 is 2 \boxed{2} .

Zach Bian
Dec 28, 2017

For people bad at geometry:

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
from math import *

def varAndPrint(variable):
    try:
        for k,v in globals().items():
            if(v == variable):
                print(k,v)
    except:
        for k,v in locals().items():
            if(v == variable):
                print(k,v)

# Begin:
# We know it's a unit circle, so it's easy to derive the coordinates of the 10 points that are not A:
pointList = []
for i in range(1,6):
    angle = 2*i*pi/11
    pointList.append({'x': cos(angle), 'y':sin(angle)})

# Basic distance formula
def dist(a,b):
    return sqrt((a['x']-b['x'])**2 + (a['y']-b['y'])**2)

# Now get the length from A to each of the other coords
accumulator = 1
for point in pointList:
    accumulator *= dist({'x':1,'y':0}, point)

print(accumulator,"squared is:",accumulator**2)
Rounded = round(accumulator**2)
varAndPrint(Rounded)
accumulator = 0
for dig in str(Rounded):
    accumulator += int(dig)
print("Sum of digits:", accumulator)

Output:

1
2
3
3.3166247903553994 squared is: 10.999999999999996
Rounded 11
Sum of digits: 2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...